A high temperature perovskite luminescent ceramic and preparation method thereof

By introducing low-melting point borosilicate glass and perovskite nanocrystals into alumina ceramics, high-temperature reaction and pressing molding methods are used to solve the problem of low color development index of rare earth fluorescent ceramics and difficult to synthesize perovskite nanocrystals. Perovskite luminescent ceramics with high luminescence efficiency and high temperature stability are produced.

CN116177994BActive Publication Date: 2025-02-07SHIJIAZHUANG TIEDAO UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210537053.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-18
Publication Date
2025-02-07
Estimated Expiration
2042-05-18

AI Technical Summary

Technical Problem

The existing technology cannot effectively solve the problems of low color rendering index, wide half-maximum, and inability to achieve full chromatographic luminescence. At the same time, perovskite nanocrystals are difficult to synthesize at high temperatures, resulting in difficult preparation of high-efficiency quantum-effect luminescent ceramics.

Method used

High-temperature perovskite luminescent ceramics are prepared by introducing low-melting point borosilicate glass powder into the alumina ceramic powder and adding synthetic perovskite nanocrystals to the composite system.

Benefits of technology

Perovskite luminescent ceramics with high luminescent efficiency retain the luminescent performance of perovskites, and also have excellent characteristics of alumina glass ceramics, such as high thermal conductivity and chemical stability, improving the high-temperature luminescent stability of perovskites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116177994B_ABST
    Figure CN116177994B_ABST
Patent Text Reader

Abstract

The present invention discloses a novel high-temperature perovskite luminescent ceramic material and a preparation method thereof, comprising the following steps: S1: ball milling ceramic powder, glass powder and synthetic perovskite raw material, and performing screening and drying to obtain a mixed powder; S2: pressing the mixed powder to obtain a luminescent ceramic blank; S3: sintering the luminescent ceramic blank to obtain a high-temperature perovskite luminescent ceramic. Compared with the prior art, the perovskite luminescent ceramic material prepared by the present invention has the characteristics of adjustable quality, stable properties and excellent comprehensive performance, which provides a new strategy for further expanding the luminescent ceramic system and optimizing its performance, and meeting a variety of service conditions, and lays a foundation for the further application of perovskite luminescent ceramics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a high-temperature perovskite luminescent ceramic and a preparation method thereof, and belongs to the technical field of luminescent ceramic materials and perovskite materials. Background Art

[0002] At present, the widely studied luminescent materials are mainly prepared based on rare earth phosphors, such as rare earth fluorescent glass, rare earth fluorescent film, rare earth fluorescent ceramics, rare earth fluorescent crystals, etc. However, rare earth phosphors have low color rendering index, large half-peak width, and cannot achieve full-color luminescence. At the same time, some rare earth materials are expensive, which limits their further application. All-inorganic perovskite nanocrystals have good photoluminescence properties, such as photoluminescence efficiency greater than 100%, narrow emission bandwidth (<20nm) and full-spectrum tunable (410-700nm entire visible spectrum region) luminescence properties, which shine in the fields of LED lighting, lasers, photodetectors, upconversion materials, solar cells, etc. These characteristics of perovskites also make them show attractive prospects in the field of luminescent materials, but there are no research reports on perovskite luminescent ceramics.

[0003] At present, the main research direction of perovskite ceramics is oxide perovskite structural ceramics, as shown in the CN110041067A patent, which focuses on solving the dielectric constant of its LTCC microwave dielectric ceramics through composition regulation. The fluorescent ceramics that are currently widely studied, such as CN112537953A, CN112047735A and other patents, are realized by compounding rare earth luminescent materials and ceramic materials, but their wavelength is within the range of 500-650 nanometers, and the wavelength range is narrow, and full-color luminescence cannot be achieved. At the same time, the rare earth materials are expensive, which limits their further application. At the same time, the CN112759267A patent mentions a perovskite nanocrystalline glass ceramic film laminated composite material, which prepares perovskite glass ceramic powder through a melting process, and then prepares a slurry to coat the surface of the substrate to obtain a laminated composite material. This preparation process is cumbersome and the luminescence performance is limited. In this context, in order to further promote the application of perovskite material systems, perovskite luminescent materials are urgently needed to be developed.

[0004] At the same time, due to the ionic properties of perovskite itself, its high-temperature stability is poor, and the raw materials for the synthesis of perovskite are also prone to decomposition at high temperatures, making it difficult to synthesize perovskite directly under high temperature conditions. These two factors determine the difficulty of preparing perovskite luminescent ceramics that achieve efficient quantum effects. However, existing technologies cannot achieve the successful preparation of luminescent ceramics. Based on this, we need to develop new material systems and process processes to obtain perovskite luminescent ceramics with high luminescence efficiency. Summary of the invention

[0005] The present invention discloses a high-temperature perovskite luminescent ceramic and a preparation method thereof, so as to solve the technical problems of low color rendering index, large half-peak width and inability to realize full-color spectrum luminescence existing in traditional rare earth luminescent ceramics, and solve the problem of difficulty in synthesizing high quantum effect perovskite nanocrystals at high temperature, and prepare perovskite luminescent ceramics with high luminescence efficiency, laying a foundation for promoting its device application.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention includes:

[0007] In the first aspect, the present invention provides a high-temperature perovskite luminescent ceramic, which includes an alumina ceramic powder, into which a low-melting-point borosilicate glass powder is introduced, and into a composite system of the alumina ceramic powder and the low-melting-point borosilicate glass powder, perovskite nanocrystals are introduced, wherein the perovskite nanocrystals are obtained by a high-temperature reaction of raw materials for synthesizing perovskite nanocrystals.

[0008] According to a preferred embodiment of the present invention, the content of the alumina ceramic powder is preferably 30-50wt.%.

[0009] According to a preferred embodiment of the present invention, the low melting point borosilicate glass powder preferably has a content of 30-50wt.%.

[0010] According to a preferred embodiment of the present invention, the perovskite nanocrystal is CsPbBr3 nanocrystal, preferably, its content is 5-30wt.%; the raw materials for synthesizing the perovskite nanocrystal are cesium carbonate, lead bromide and sodium bromide.

[0011] In a second aspect, the present invention provides a method for preparing a high-temperature perovskite luminescent ceramic, comprising:

[0012] First, alumina ceramic powder, low melting point borosilicate glass powder and raw materials for synthesizing perovskite nanocrystals are ball-milled and mixed; then the mixture is pressed into a luminescent ceramic blank by a pressing method, and then the luminescent ceramic blank is sintered to obtain a high-temperature perovskite luminescent ceramic.

[0013] Preferably, the content of alumina ceramic powder is 30-50wt.%.

[0014] Preferably, the content of low melting point borosilicate glass powder is 30-50wt.%.

[0015] Preferably, the perovskite nanocrystals are CsPbBr3 nanocrystals, and the content thereof is 5-30wt.%.

[0016] According to a preferred embodiment of the present invention, the method comprises:

[0017] S1, ball-milling alumina ceramic powder, low-melting-point borosilicate glass powder and raw materials for synthesizing perovskite nanocrystals, and performing sieving and drying to obtain a mixed powder;

[0018] S2: Pressing the mixed powder into a shape to obtain a luminescent ceramic blank;

[0019] S3: Sintering the luminescent ceramic green body to obtain a high-temperature perovskite luminescent ceramic.

[0020] According to a preferred embodiment of the present invention, the raw materials for synthesizing perovskite nanocrystals are cesium carbonate powder, lead bromide powder and sodium bromide powder, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2.

[0021] According to a preferred embodiment of the present invention, in S1, the particle size of the alumina ceramic powder is 50nm-5μm; the particle size of the low-melting-point borosilicate glass powder is 0.5-5μm.

[0022] According to a preferred embodiment of the present invention, in S1, preferably, the ball milling is a drum ball milling method, the grinding balls are zirconium oxide, the material-ball ratio is 1:1-1:3, and the ball milling time is 12-24h.

[0023] According to a preferred embodiment of the present invention, in S1, the drying treatment temperature is 50-100°C and the time is 12-24h.

[0024] According to a preferred embodiment of the present invention, in S2, preferably, the pressing method is a dry pressing method, the pressure is 20-30 MPa, and the holding time is 1-5 min.

[0025] According to a preferred embodiment of the present invention, in S2, the pressure is 30 MPa and the holding time is 3 min.

[0026] According to a preferred embodiment of the present invention, in S3, preferably, the sintering process is pressureless sintering, the heating rate is 1°C / min-5°C / min, the sintering temperature is 700-950°C, and the holding time is 1-4h.

[0027] According to a preferred embodiment of the present invention, in S3, the sintering temperature is 750°C.

[0028] In a third aspect, the present invention also relates to a high-temperature perovskite luminescent ceramic, which is prepared by the method of any of the above embodiments.

[0029] Compared with the prior art, the advantages of the present invention are:

[0030] (1) The high-temperature perovskite luminescent ceramic provided by the present invention uses cesium carbonate, lead bromide and sodium bromide as raw material powders to form perovskite nanocrystals, and alumina and low-melting-point borosilicate glass powder as a matrix, and the preparation of perovskite luminescent ceramics is achieved through high-temperature treatment. At the same time, the ceramic material preserves the luminescent properties of perovskite, and also retains the excellent properties of alumina glass ceramics itself, such as high thermal conductivity, high chemical stability and low sintering temperature.

[0031] (2) At the same time, this experiment prepared high-temperature perovskite luminescent ceramic materials with controllable quality, stable properties and excellent comprehensive performance through a simple and easy-to-promote process, which improved the high-temperature luminescence stability of perovskite, provided a new strategy for further expanding the luminescent ceramic system and optimizing its performance to meet diverse service conditions, and laid the foundation for the further application of perovskite luminescent ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the morphology of the ceramic sample of Example 1

[0033] Figure 2 This is the fluorescence irradiation morphology of the sample in Example 1

[0034] Figure 3 XRD pattern of sample 1

[0035] Figure 4 PL test result of sample 1

[0036] Figure 5 Example 2 Ceramic sample morphology

[0037] Figure 6 Example 2: Fluorescence irradiation morphology of the sample

[0038] Figure 7 XRD pattern of sample 2

[0039] Figure 8 Example 3 Ceramic sample morphology

[0040] Fig. 9 Example 3: Fluorescence irradiation morphology of the sample

[0041] Fig.10 Example 4 Ceramic sample morphology

[0042] Fig.11 Example 4 Fluorescence irradiation morphology of ceramic samples

[0043] Fig.12 Example 5 Ceramic sample morphology

[0044] Fig.13 Example 5: Fluorescence irradiation morphology of ceramic samples

[0045] Fig.14 Comparative Example 1 Ceramic sample morphology

[0046] Fig.15 Comparative Example 1 Fluorescence irradiation morphology of ceramic samples

[0047] Fig.16 Comparative Example 2 Ceramic Sample Morphology

[0048] Fig.17 Comparative Example 2 Fluorescence irradiation morphology of ceramic samples DETAILED DESCRIPTION

[0049] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0050] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0051] Example 1:

[0052] S1: Weigh alumina ceramic powder, borosilicate glass powder and raw materials for synthetic perovskite and mix them by drum ball milling, and obtain a mixture after sieving and drying. Among them, the particle size of alumina powder is 50nm, and its content is 40wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 35wt.%; the total content of raw materials for synthetic perovskite is 25wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding balls to raw materials is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0053] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0054] S3: The obtained luminescent ceramic blank is placed in a muffle furnace, heated to 750°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain the perovskite luminescent ceramic.

[0055] After sintering, the ceramic samples Figure 1 As shown in Figure 1, the surface appears slightly yellow. When the sample is illuminated by violet light, Figure 2 As shown, it shows a strong bright green color, which fully proves that the luminescent ceramic has good fluorescence. After the block was ground into powder, X-ray diffraction test, steady-state transient fluorescence spectrum (PL) and neutron diffraction were carried out respectively. The results are as follows Figure 3 , Figure 4 and Figure 5 As shown. Figure 3 By comparing with the PDF standard card, it can be determined that CsPbBr3 is generated in the ceramic, which means that the ceramic generates green-emitting CsPbBr3 nanocrystals during the high-temperature treatment at 750℃. Figure 4 It can be seen from the fluorescence spectrum that there is a fluorescence peak in the figure and the peak position is 514nm, which is the peak position of CsPbBr3 perovskite.

[0056] In summary, the perovskite fluorescent ceramics prepared by this method have fluorescent properties, and the fluorescence of the composite material is uniform.

[0057] Example 2

[0058] S1: Weigh alumina ceramic powder, borosilicate glass powder and raw materials for synthetic perovskite and mix them by drum ball milling, and then sieve and dry them to obtain a mixture. Among them, the particle size of alumina powder is 50nm, and its content is 48wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 42wt.%; the total content of raw materials for synthetic perovskite is 10wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding balls to raw materials is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0059] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0060] S3: The obtained luminescent ceramic blank is placed in a muffle furnace, heated to 750°C at a heating rate of 5°C / min, kept at this temperature for 2 hours, and cooled in the furnace to obtain the perovskite luminescent ceramic.

[0061] The morphology of the ceramic sample after sintering is shown in Figure 2. Figure 5 As shown in Figure 1, the sample surface appears slightly yellow. When the sample is illuminated by purple light, Figure 6 As shown, it shows a strong bright green color, which fully proves that the luminescent ceramic has good fluorescence. After the block is ground into powder, the X-ray diffraction test results are as follows Figure 7 As shown. Figure 7 By comparing with the PDF standard card, it can be determined that CsPbBr3 is generated in the ceramic. From this, it can be known that the ceramic generates green-emitting CsPbBr3 nanocrystals with good fluorescence properties during the high-temperature treatment process at 750℃.

[0062] Example 3

[0063] Alumina ceramic powder, borosilicate glass powder and raw materials of synthetic perovskite are weighed and mixed by drum ball milling, and then sieved and dried to obtain a mixture. Among them, the particle size of alumina powder is 50nm, and its content is 40wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 35wt.%; the total content of raw materials of synthetic perovskite is 25wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding ball to raw material is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0064] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0065] S3: placing the obtained luminescent ceramic blank in a muffle furnace, heating it to 900°C at a heating rate of 5°C / min, keeping it at that temperature for 2h, and cooling it along with the furnace to obtain the perovskite luminescent ceramic.

[0066] After sintering, the ceramic samples Figure 8 As shown in Figure 1, the sample surface appears slightly yellow. When the sample is illuminated by purple light, Fig. 9 As shown, it exhibits a uniform bright green color, which fully proves that the luminescent ceramics have fluorescence.

[0067] Example 4

[0068] Alumina ceramic powder, borosilicate glass powder and raw materials of synthetic perovskite are weighed and mixed by drum ball milling, and then sieved and dried to obtain a mixture. Among them, the particle size of alumina powder is 50nm, and its content is 48wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 42wt.%; the total content of raw materials of synthetic perovskite is 10wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding ball to raw material is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0069] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0070] S3: placing the obtained luminescent ceramic blank in a muffle furnace, heating it to 700°C at a heating rate of 5°C / min, keeping it at that temperature for 2h, and cooling it along with the furnace to obtain the perovskite luminescent ceramic.

[0071] After sintering, the ceramic samples Fig.10 As shown in Figure 1, the surface appears slightly yellow. When the sample is illuminated by violet light, Fig.11 As shown, it exhibits a strong bright green color, which fully proves that the luminescent ceramic has good fluorescence.

[0072] Example 5

[0073] Alumina ceramic powder, borosilicate glass powder and raw materials of synthetic perovskite are weighed and mixed by drum ball milling, and then sieved and dried to obtain a mixture. Among them, the particle size of alumina powder is 50nm, and its content is 48wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 42wt.%; the total content of raw materials of synthetic perovskite is 10wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding ball to raw material is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0074] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0075] S3: placing the obtained luminescent ceramic blank in a muffle furnace, heating it to 800°C at a heating rate of 5°C / min, keeping it at that temperature for 2h, and cooling it along with the furnace to obtain the perovskite luminescent ceramic.

[0076] After sintering, the ceramic samples Fig.12 As shown in Figure 1, the sample surface appears slightly yellow. When the sample is illuminated by purple light, Fig.13 As shown, it exhibits a strong bright green color, which fully proves that the luminescent ceramic has good fluorescence.

[0077] Comparative Example 1

[0078] Alumina ceramic powder, borosilicate glass powder and raw materials of synthetic perovskite are weighed and mixed by drum ball milling, and then sieved and dried to obtain a mixture. Among them, the particle size of alumina powder is 50nm, and its content is 40wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 35wt.%; the total content of raw materials of synthetic perovskite is 25wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding ball to raw material is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0079] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0080] S3: placing the obtained luminescent ceramic blank in a muffle furnace, heating it to 1000°C at a heating rate of 5°C / min, keeping it at that temperature for 2h, and cooling it along with the furnace to obtain the perovskite luminescent ceramic.

[0081] After sintering, the ceramic samples Fig.14 As shown, the surface appears white. When the sample is illuminated by violet light, Fig.15As shown, the sample appears black as a whole, with only a weak fluorescence at the fracture, proving that excessively high temperature will lead to a weakening of the fluorescence performance.

[0082] Comparative Example 2

[0083] Alumina ceramic powder, borosilicate glass powder and raw materials of synthetic perovskite are weighed and mixed by drum ball milling, and then sieved and dried to obtain a mixture. Among them, the particle size of alumina powder is 50nm, and its content is 52wt.%; the particle size of borosilicate glass powder is 5μm, and its content is 45wt.%; the total content of raw materials of synthetic perovskite is 3wt.%, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:2; the ratio of zirconium oxide grinding ball to raw material is 1:2, and the ball milling time is 12h; the drying temperature is 60℃, and the drying time is 12h.

[0084] S2: The mixed material is pressed on a pressure forming machine to obtain a luminescent ceramic blank, wherein the pressure is 25 MPa and the pressure holding time is 3 minutes.

[0085] S3: placing the obtained luminescent ceramic blank in a muffle furnace, heating it to 700°C at a heating rate of 5°C / min, keeping it at that temperature for 2h, and cooling it along with the furnace to obtain the perovskite luminescent ceramic.

[0086] After sintering, the ceramic samples Fig.16 As shown, the surface appears white. When the sample is illuminated by violet light, Fig.17 As shown, it appears black and no fluorescence is found in the sample.

[0087] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician who makes slight changes or modifications using the technical contents disclosed above without departing from the scope of the technical solution of the present application is equivalent to an equivalent implementation case and is within the technical scope.

Claims

1. A high-temperature perovskite luminescent ceramic, characterized in that: It includes alumina ceramic powder, low melting point borosilicate glass powder is introduced into the alumina ceramic powder, perovskite nanocrystals are introduced into the composite system of the alumina ceramic powder and the low melting point borosilicate glass powder, and the perovskite nanocrystals are obtained by high temperature reaction of raw materials for synthesizing perovskite nanocrystals.

2. The high temperature perovskite luminescent ceramic according to claim 1, characterized in that: The perovskite nanocrystal is CsPbBr3 nanocrystal; the raw materials for synthesizing the perovskite nanocrystal are cesium carbonate, lead bromide and sodium bromide.

3. A method for preparing a high-temperature perovskite luminescent ceramic according to claim 1, characterized in that: The steps include: S1, ball-milling alumina ceramic powder, low-melting-point borosilicate glass powder and raw materials for synthesizing perovskite nanocrystals, and performing sieving and drying to obtain a mixed powder; S2: Pressing the mixed powder into a shape to obtain a luminescent ceramic blank; S3: Sintering the luminescent ceramic green body to obtain a high-temperature perovskite luminescent ceramic.

4. The method for preparing the high temperature perovskite luminescent ceramic according to claim 3, characterized in that: The perovskite nanocrystal is CsPbBr3 nanocrystal.

5. The method for preparing high-temperature perovskite luminescent ceramics according to claim 3, characterized in that: In S1, the raw materials for synthesizing perovskite nanocrystals are cesium carbonate powder, lead bromide powder and sodium bromide powder, and the ratio of cesium carbonate, lead bromide and sodium bromide is 1:2:

2.

6. The preparation method according to claim 3, characterized in that: In S1, the particle size of the alumina ceramic powder is 50nm-5μm; the particle size of the borosilicate glass powder is 0.5-5μm.

7. The method for preparing high-temperature perovskite luminescent ceramics according to claim 3, characterized in that: In S1, the ball milling is a drum ball milling method, the grinding balls are zirconium oxide, the material-to-ball ratio is 1:1-1:3, and the ball milling time is 12-24 hours.

8. The method for preparing high-temperature perovskite luminescent ceramics according to claim 3, characterized in that: In S1, the drying treatment temperature is 50-100°C and the time is 12-24h.

9. The preparation method according to claim 3, characterized in that: In S2, the pressing method is a dry pressing method, the pressure is 20-30 MPa, and the holding time is 1-5 min.

10. The preparation method according to claim 3, characterized in that: In S3, the sintering treatment is pressureless sintering, the heating rate is 1°C / min-5°C / min, the sintering temperature is 700-950°C, and the holding time is 1-4h.

11. The preparation method according to claim 10, characterized in that: In S3, the sintering temperature is 750°C.

Citation Information

Patent Citations

  • Low-dielectric high-Q temperature-stable perovskite structure LTCC (Low Temperature Co-Fired Ceramic) microwave dielectric material and preparation method thereof

    CN110041067A

  • Multiphase fluorescent ceramic material and preparation method thereof

    CN112047735A

  • Composite fluorescent ceramic and preparation method thereof

    CN112537953A